The associations between dietary intakes from 36 to 60 months of age and primary dentition non‐cavitated caries and cavitated caries. (8th November 2012) - Chankanka, Oitip; Levy, Steven M.; Marshall, Teresa A.; Cavanaugh, Joseph E.; Warren, John J.; Broffitt, Barbara; Kolker, Justine L.
Abstract: Objective: To examine risk factors for non‐cavitated caries, as well as cavitated caries. Methods: Subjects were participants in the Iowa Fluoride Study cohort. Dietary data were collected at 36, 48, and 60 months old using 3‐day dietary diaries, and a dental examination was conducted at about age 5. We compared the frequencies of dietary intakes of three groups: a) children having only d1 caries ( n = 41); b) children having only cavitated (d2+ f) caries ( n = 46); and c) children having both d1 and d2+ f caries ( n = 49) with a forth group; d) those of caries‐free children ( n = 257). Results: Multinomial and binomial logistic regression was used, where the categorical outcome was based on the 4 caries groups, and the caries‐free group was designated as the reference. In the final model, sevenvariables were associated with the caries outcome. Lower milk consumption frequency at meals and greater presweetened cereal consumption frequency at meals were significantly associated with a greater likelihood of being in the d1 group. Greater regular soda pop consumption frequency and greater added sugar consumption frequency at snacks were significantly associated with being in the cavitated caries (d2+ f and/or d1 d2+ f) groups. Lower socioeconomic status and less frequent toothbrushing increased the likelihood of being in the d1 group. Conclusions: The results suggest that different food and beverage categories are associated with being in the d1 group compared with the cavitated caries groups. More frequent toothbrushing, greater milk consumption at meals, and avoiding presweetened cereal consumption at meals might reduce the risk of developing non‐cavitated caries.